Developing a research agenda for reducing the stigma of addictions, part II: Lessons from the mental health stigma literature. (22nd November 2016) - Corrigan, Patrick W.; Schomerus, Georg; Shuman, Valery; Kraus, Dana; Perlick, Debbie; Harnish, Autumn; Kulesza, Magdalena; Kane‐Willis, Kathleen; Qin, Sang; Smelson, David
Abstract : Background and Objectives: Although advocates and providers identify stigma as a major factor in confounding the recovery of people with SUDs, research on addiction stigma is lacking, especially when compared to the substantive literature examining the stigma of mental illness. Methods: A comprehensive review of the stigma literature that yielded empirically supported concepts and methods from the mental health arena was contrasted with the much smaller and mostly descriptive findings from the addiction field. In Part I of this two part paper (American Journal of Addictions, Vol 26, pages 59–66, this issue), constructs and methods from the mental health stigma literature were used to summarize research that seeks to understand the phenomena of addiction stigma. Results: In Paper II, we use this summary, as well as the extensive literature on mental illness stigma change, to outline a research program to develop and evaluate strategies meant to diminish impact on public and self‐stigma (eg, education and contact). Conclusions and Scientific Significance: The paper ends with recommendations for next steps in addiction stigma research. (Am J Addict 2017;26:67–74)